2016
DOI: 10.47513/mmd.v8i2.485
|View full text |Cite
|
Sign up to set email alerts
|

The Bonny Method of Guided Imagery and Music for Medical Populations: Evidence for Effectiveness and Vision for the Future

Abstract: The Bonny Method of Guided Imagery and Music (GIM) and modifications derived from it are potent and flexible for addressing a variety of psychological and physical concerns in both clinical and nonclinical adult populations. This paper summarizes the existing evidence relevant to medical populations with a focus on mental and physical health. Medical populations found to benefit from a series of individual GIM sessions have included individuals with cancer, cardiovascular disease, autoimmune disorders, and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Jordanger (2015) explored the possibilities with BMGIM related to conflict transformation. Devised by Helen Bonny (1975), BMGIM is an approach that has demonstrated success with traumatized clients, including psychiatric patients (McKinney & Grocke, 2016) and war survivors (Ng, 2005). As it requires advanced training, BMGIM utilizes more refined induction techniques than those in the vignette, and combines them with supportive music listening (Bonny, 1975).…”
Section: Reflection Cmentioning
confidence: 99%
“…Jordanger (2015) explored the possibilities with BMGIM related to conflict transformation. Devised by Helen Bonny (1975), BMGIM is an approach that has demonstrated success with traumatized clients, including psychiatric patients (McKinney & Grocke, 2016) and war survivors (Ng, 2005). As it requires advanced training, BMGIM utilizes more refined induction techniques than those in the vignette, and combines them with supportive music listening (Bonny, 1975).…”
Section: Reflection Cmentioning
confidence: 99%
“…She recommended that if the client has severe fatigue or if talking would 'un-do' the relaxation, the therapist may defer verbal processing to a later time, and encourage the patient to rest quietly (West, 2015). McKinney and Grocke's (2018) review of GIM for medical populations also found that adaptations of GIM to meet patients' needs are possible without sacrificing clinical effectiveness.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…GIM therapists have described modifications and adaptations of the method and benefits and goals in using GIM with medical patients (Abrams & Kasayka, 2005;Bruscia, 2015;Burns, 2001;McKinney & Grocke, 2016). What is not known, however, is the depth of GIM practiced with medical populations.…”
Section: The Depth Of Gimmentioning
confidence: 99%